2008
DOI: 10.1111/j.1349-7006.2008.00749.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between NDRG1 and PTEN expression in endometrial carcinoma

Abstract: N-myc Downstream-Regulated Gene 1 (NDRG1) is known as a differentiation-related gene that plays important roles in cell differentiation, organ formation, and embryonic development. NDRG1 has recently been shown to be associated with carcinogenesis and tumor progression in a wide variety of tumors. Phosphatase and tensin homolog deleted from chromosome (PTEN), a phosphatase and tensin homolog located on chromosome 10, is shown to be a tumor suppressor and is often mutated or deleted in various tumor cells, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The expression of NDRG1/Cap43 is often elevated in various types of malignant solid tumors, such as the lung, brain, skin, kidney, liver, and breast [11,12] and endometrial carcinoma [13], compared with their concordant normal tissues. Furthermore, expression of NDRG1/Cap43 was significantly higher in poorly differentiated carcinoma than well-differentiated carcinoma of the colon [14] and liver [15].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of NDRG1/Cap43 is often elevated in various types of malignant solid tumors, such as the lung, brain, skin, kidney, liver, and breast [11,12] and endometrial carcinoma [13], compared with their concordant normal tissues. Furthermore, expression of NDRG1/Cap43 was significantly higher in poorly differentiated carcinoma than well-differentiated carcinoma of the colon [14] and liver [15].…”
Section: Introductionmentioning
confidence: 99%
“…NDRG1 protein expression has been described to be present in normal brain or brain tumor tissue [11] as well as being an important gene that is playing an active role in the regulation of a broad spectrum of human cancer diseases like human gastric cancer, squamous cell carcinomas, breast cancer, human hepatocellular carcinoma, brain tumors and leukemia [12][13][14][15][16][17][18][19][20][21][22] . NDRG1 was suggested to be a prognostic marker for hypoxic regions within a tumor mass because of its stability as a protein [23][24][25] and because it is highly expressed in malignant tumor tissues compared to normal tissue of the same origin [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown down-regulation of NDRG1 in tumors of colon [12], breast [13] and prostate [4,9]. In contrast, NDRG1 up-regulation has been reported in hepatocellular carcinoma [14], renal cell carcinoma [15,16], and endometrial cancer [17]. NDRG1's function and regulation in cancerous human ovary is not clear.…”
Section: Introductionmentioning
confidence: 96%